Actors’ Contestation in Responding to Government Policies Regarding Development of Broiler Poultry Farming Business: A Case from Blitar, East Java, Indonesia - Saud, Muhammad Yamin; Ali, Muhammad Saleh S.; Sulaiman, Amran; Junaiddin, Makmun; Rahmadanih, Rahmadanih (Hasanuddin University, 2023)
This study examines the contestation among actors responding to government policies in broiler farming. The research method employed is qualitative. A comprehensive investigation into each actor’s characteristics allows for a thorough understanding of unfolding contestation. The study took place in Blitar, East Java, Indonesia. The results indicate three key actors: the integrator farm, the independent farm, and the family farm. An integrator functions as an investor; while an independent consists of breeders with land, resources, and labour. Family farmers are operated by individuals with limited production capacities. The government, aiming to ensure a stable supply of livestock for domestic consumption, utilizes its legislative authority to facilitate investment prospects in Indonesia. Integrator farmers seize this opportunity to dominate broiler arming, compelling their actors to align with their interests. Independent farmers safeguard their interests through collaborative partnerships, whereas family farmers can only express their discontent with the government through protests.